2021
DOI: 10.21037/apm-20-1548
|View full text |Cite
|
Sign up to set email alerts
|

Discussing diabetes, palliative and end of life care: choosing the ‘right’ language

Abstract: Background: Palliative care and advance care planning are important components of diabetes and other chronic disease management plans. Most people with diabetes do not have conversations about palliative/end of life (EOL) care or advance care directives; often because diabetes clinicians are reluctant to discuss these issues. Guidelines for conversations and decision aids can assist shared decision-making for both clinicians and patients. The aim was to co-design information with older people with diabetes, fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 26 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…Word choice represents an opportunity for clinicians to honor patient and family preferences for communication. Interviews with patients and family members suggest that they want clinicians to use clear language 14 , 15 , 16 , 17 , 18 , 19 , 20 even when it is hard to hear in the moment. 21 However, many clinicians worry that words like die , death , or dying may be perceived as harsh 16 and prefer to match the language used by patients and families.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Word choice represents an opportunity for clinicians to honor patient and family preferences for communication. Interviews with patients and family members suggest that they want clinicians to use clear language 14 , 15 , 16 , 17 , 18 , 19 , 20 even when it is hard to hear in the moment. 21 However, many clinicians worry that words like die , death , or dying may be perceived as harsh 16 and prefer to match the language used by patients and families.…”
Section: Discussionmentioning
confidence: 99%
“… 21 However, many clinicians worry that words like die , death , or dying may be perceived as harsh 16 and prefer to match the language used by patients and families. 17 , 49 Our design did not allow for direct assessment of family preferences, including whether acknowledging death using the word itself a single time or mirroring the language used by family members is sufficient. Given that we found that most references to death made by family members were euphemistic, future work should prioritize assessing family preferences for language use.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations